IDENTIFICATION AND CHARACTERIZATION OF THE SUPPRESSOR PROTEIN HC-PRO IN PVY-INFECTED POTATO PLANTS OF KAZAKHSTANI SELECTION - Zhakmanova, Y.A.; Khosnutdinova, T.S.; Sutula , M.Y. (Eurasian Journal of Applied Biotechnology, 2024)
Plant viruses pose a serious threat to all agricultural crops, leading to significant yield reduction, deterioration of seed quality, and degradation of cultivars. Potato infection with Potato virus Y (PVY) during the growing season causes severe damage, including leaf curling, leaf spot, and stunted growth due to shortened internodes and ring necrosis of tubers. In recent years, Kazakhstan has seen an increase in aphid populations, the main vectors of plant viruses. Therefore, it is crucial to conduct research on the diagnosis and identification of viral diseases. RNA interference (RNAi) plays a vital role in plant defense against viral infections. Viruses produce suppressor proteins to counteract RNAi, blocking plant defense mechanisms. The structural features of viral suppressors determine their specific functions in efficiently suppressing RNA interference. The HC-Pro protein is one such suppressor, aiding in virus spread and neutralizing plant-synthesized siRNA. In this study, using various methods including visual diagnostics, enzyme-linked immunosorbent assay (ELISA), chromatographic purification of plant extracts infected with PVY, Western blot, and enzymatic reaction with specific HC-Pro antibodies, the suppressor protein HC-Pro encoded by PVY was detected and identified.